Development of Pakal Forest Park as a Sustainable Edu-Ecotourism and Family Recreation Destination in Surabaya - Hadi, Bawa Mulyono; Taufiq, Achmad; Mau, Daniel Pandu (Transpublika Publisher, 2026)
Urban green spaces play a critical role in ecological sustainability, public health, and social well-being, especially in rapidly urbanizing regions. This study examines Taman Hutan Pakal, an urban forest in West Surabaya, to explore its potential as a sustainable edu-ecotourism and family recreation destination from a management and innovation perspective. Data were collected through field observations, in-depth interviews with park managers, visitors, local communities, and urban planning experts, as well as document analysis. Thematic analysis identified four key insights. First, Taman Hutan Pakal possesses significant ecological and recreational potential. Second, existing challenges include insufficient family-oriented infrastructure, limited environmental education programs, and low visibility in public engagement. Third, opportunities exist through societal demand and supportive policies to enhance environmental literacy and healthy recreational practices. Fourth, strategic interventions such as branding as an Educational Urban Forest, implementing biodiversity-based environmental education, improving child-friendly facilities, and fostering multi-stakeholder collaboration enable value transformation, innovation in urban park management, and long-term sustainability. The findings highlight the importance of integrating ecological, social, and educational dimensions in urban green space management to generate community well-being and strategic value for regional development.